Productivity analysis of aerobic rice in the lowlands of Southern Kerala - Jinsy, V.S.; Shalini Pillai, P.; Jacob, J. (Journal of Tropical Agriculture, 2015)
A field experiment was conducted at the Cropping Systems Research Centre, Karamana, Kerala to assess the adaptability and water productivity of aerobic rice system in the lowlands of southern Kerala. The water productivity of four rice varieties [PTB 52 (Aiswarya), MO 16 (Uma), MAS 946-1 (Sharada) and PMK (R) 3] were studied under two moisture regimes – aerobic (30 per cent depletion of available soil moisture) and flooded conditions. The experiment was laid out in randomized block design, with five replications, under both the moisture regimes. Aerobic rice recorded higher water productivity (0.68 kg m-3) than the conventional flooded rice (0.42 kg m-3). The variety, MAS 946-1 recorded the highest water productivity of 0.60 kg m-3. Among the four varieties tested, MAS 946-1, the first aerobic rice variety released from UAS, Bengaluru and the KAU rice varieties Aiswarya and Uma, proved superior for aerobic conditions in southern Kerala.